Implementación de métodos estadísticos para la clasificación de las relaciones máxilo-mandibulares clase I - Jaramillo-V., Pedro María; Sora-B., Carolina; Villegas-M., Natalia (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The purpose of this study was to apply statistical tools in the classification of maxillary-mandibular class I relationship using the variables of the analysis of the lateral cephalic x-ray. The sample consisted of a total 103 subjects (51 men / 52 women), between the ages of 18 and 29 years, belonging to the student population of the University of Antioquia in Medellin, with bilateral molar and canine class I relationship, without evident crowding and good facial balance. The cephalometric measures used were divided in two groups: skeletal measures and dentoalveolar measures. The data was processed and the different statistical analyses were carried out: univariate, bivariate and multivariate. The results showed great dispersion of the data and hence a heterogeneous behavior of the sample.